Корекція метаболічних порушень у профілактиці та лікуванні діабетичної ретинопатії - Михальчик, Сергій Валерійович; Mykhalchyk, S. V. (Запорізький державний медичний університет, 2018)
Дисертаційне дослідження присвячене підвищенню ефективності профілактики та лікування діабетичної ретинопатії шляхом корекції метаболічних порушень у хворих з інсуліннезалежним цукровим діабетом на основі коротколанцюгових каротиноїдів. Для корекції АОС у хворих на інсуліннезалежний діабет і підвищення ефективності лікування, крім традиційного лікування в комплекс лікування було включено препарат групи коротколанцюгових каротиноїдів «Мультікаренол-6», що з успіхом використовується для лікування вікової макулярної дегенерація та дистрофічних змін ока. Препарат коротколанцюгових каротиноїдів у хворих на міопію призначався за схемою: по одній 1 чайній ложці двічі на день під час їжі, протягом 45 днів, чотири курси на рік. Запропонований спосіб лікування діабетичної ретинопатії «Спосіб профілактики та лікування діабетичної ретінопатії у хворих на інсуліннезалежний цукровий діабет» в співавт. з Завгородня Н.Г., Пат. № 87687 UA № u201311774. Включення в комплексну терапію коротколанцюгових каротиноїдів (лікопіну) сприяє гальмуванню розвитку ДРП та приводить до поліпшення зорових функцій, а саме: підвищення гостроти зору в 90% очей, проти 68 % у групі контролю (р<0,05), підвищення світлочутливості сітківки в зоні 0-10 градусів на 42%, проти 25% у групі контролю (р<0,05), стабілізує зорові функції в 38% очей, проти 14% у групі контролю. (р<0,05). The dissertation is devoted to the effectiveness increase in prevention and treatment of diabetic retinopathy for patients with insulin-dependent diabetes mellitus and correction of antioxidant system disorders (AOS) by short-chain drugs based on new scientific data on the peculiarities of changes in antioxidant processes in patients' blood depending on the stage. The relationship between oxidative stress activation, NO dysfunction and the factors regulating angiogenesis in the formation of diabetic retinopathy is first shown. It has been shown for the first time that the antioxidant from the group of short-chain carotenoids can cause regression of molecular-biochemical and clinical signs of retinopathy in patients with insulin-dependent diabetes mellitus. It was first established that under the action of AOS of short-chain carotenoids, the expression of key molecular regulators of angiogenesis-pigmentary factor of epithelial origin (PEDF) and vascular endothelial growth factor (VEGF) -regulations, as well as indicators of the NO-expression of iNOS expression and the maintenance of a stable metabolite NO-was normalized. It has been established that this effect of the drug is associated with inhibition of AFK-dependent mechanisms of retinopathy and inhibition of oxidative stress reactions (reduction of markers of oxidative modification of protein) against the background of increased activity of antioxidant enzymes-SOD, catalase and GPR. It was shown that the addition to the complex therapy of short-chain carotenoids led to a decrease in the symptoms of retinopathy in patients with diabetes and allowed the inclusion of short-chain carotenoids in the traditional treatment of patients with DR of various stages and to assess its effect on the normalization of the state of AOC, as well as significantly improve and stabilize the visual functions.
Correction of metabolic disorders in the prevention and treatment of diabetic retinopathy
Keywords: діабетична ретинопатія; метаболічні порушення; профілактика; лікування; коротколанцюгові каротиноїди; diabetic retinopathy; antioxidant system; short-chain carotenoid drug; visual functions